2022
DOI: 10.1155/2022/7622392
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Model for Automated Chinese Word Segmentation and POS Tagging

Abstract: Chinese natural language processing tasks often require the solution of Chinese word segmentation and POS tagging problems. Traditional Chinese word segmentation and POS tagging methods mainly use simple matching algorithms based on lexicons and rules. e simple matching or statistical analysis requires manual word segmentation followed by POS tagging, which leads to the inability to meet the practical requirements for label prediction accuracy. With the continuous development of deep learning technology, data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Sharma, et al [52] demonstrated experimentally that the hierarchical finetuning method has potential for development. TL with AlexNet has enabled advances in various fields, including natural language processing [53,54], where researchers used the network's features to extract meaningful representations from text data.…”
Section: Applicationsmentioning
confidence: 99%
“…Sharma, et al [52] demonstrated experimentally that the hierarchical finetuning method has potential for development. TL with AlexNet has enabled advances in various fields, including natural language processing [53,54], where researchers used the network's features to extract meaningful representations from text data.…”
Section: Applicationsmentioning
confidence: 99%